Lenguaje, derecho y significados sociales : contribuciones de la antropología lingüística al estudio del derecho - Mertz, Elizabeth (2015)
Scholars who study the social constitution of law have increasingly come to appreciate the importance of language in legal processes. This review considers the question, what difference does this attention to language make? I discuss a number of ways of approaching language, suggesting that some are more useful than others for social and legal analysis. In particular, I focus on the contribution of anthropological approaches and two recent works: Getting justice and getting even: legal consciousness among working-class Americans, by Sally Engle Merry, and Rules versus relationships: the ethnography of legal discourse, by John M. Conley and William M. O'Barr. The first section of the essay gives an overview of anthropological and linguistic approaches. The second section focuses on the study of language and law.